The Relationship Between Self-Esteem and Achievement from the Perspective of Islamic Counseling: A Literature Analysis of 2024 - Suhertina, Suhertina (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
This study explores the relationship between self-esteem, achievement, and Islamic counseling through a systematic literature review. By analyzing 10 selected articles published in 2024, the study highlights the critical role of self-esteem in academic success. Students with healthy self-esteem demonstrate better self-efficacy, resilience, and motivation to achieve their academic and career goals. Islamic counseling emerges as an effective intervention, addressing emotional and behavioral challenges while providing a strong spiritual foundation. The findings reveal that Islamic counseling not only enhances mental health but also fosters self-esteem and intrinsic motivation through the integration of spiritual and academic values. Key themes include the significant impact of self-esteem on achievement, the holistic effectiveness of Islamic counseling, and the synergy between spiritual and formal education. The study emphasizes the need for educational institutions to integrate Islamic counseling into support services, practitioners to adopt faith-based interventions, and curricula to incorporate spiritual values. These strategies can create a holistic learning environment that balances academic excellence and emotional well-being. This research provides a foundation for further exploration of Islamic counseling’s role in broader educational and psychological contexts.